2017
DOI: 10.1108/jmtm-05-2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Success factors and barriers to implementing lean in the printing industry

Abstract: Purpose Lean principles are applied in manufacturing and service industries extensively, but its successful application in the printing industry has been poor. The purpose of this paper is to explore the factors that impede the uptake of lean in the printing industry. Design/methodology/approach Qualitative case study research methods were used to explore success factors and barriers to implementing lean in printing by interviewing two managers and three employees at each of two printing firms that had imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 49 publications
1
35
0
3
Order By: Relevance
“…We observed that although LM practices on a conceptual level can be carried out without the help of IT, however, AMT as a major subcategory of IT is crucial to the higher degree of leanness. In general, LM practices are information-intensive (Ainul Azyan et al, 2017;Perez-Arostegui et al, 2012;Riezebos et al, 2009). LM uses extensive amount of information to continuously identify unproductive processes and eliminate anything that fails to add value and that is therefore considered waste (Moyano-Fuentes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that although LM practices on a conceptual level can be carried out without the help of IT, however, AMT as a major subcategory of IT is crucial to the higher degree of leanness. In general, LM practices are information-intensive (Ainul Azyan et al, 2017;Perez-Arostegui et al, 2012;Riezebos et al, 2009). LM uses extensive amount of information to continuously identify unproductive processes and eliminate anything that fails to add value and that is therefore considered waste (Moyano-Fuentes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LM has also been studied in the small and medium-sized enterprise (SME) environment. Several authors have conducted research on LM in SMEs, such as critical success factors (CSFs) [5,7,8]; enablers and inhibitors [6,10]; frameworks, road maps, and methodologies [11][12][13][14][15][16][17]; and LM implementation in SMEs [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Management and leadership commitment are crucial foundation for the introduction of lean in the organization, as several literatures have reported its significance in a timely of changes and organisational transformation (Laureani & Antony, 2012). In order to evaluate readiness for lean deployment more efficiently within SMEs, such businesses should have a good leadership qualities on ground characterized by demonstration exceptional management styles which will foster effective skills, motivation and knowledge enhancement within their employees (Hanizan et al, 2006). The willingness of leadership and management in promoting quality practices that will facilitate lean deployment and may avoid issues of unsuccessful lean implementation.…”
Section: Management and Leadership Commitmentmentioning
confidence: 99%